2023
DOI: 10.1159/000531739
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Changes following Facemask Placement in Infants Born at ≥32+0 Weeks of Gestation

Shiraz Badurdeen,
Elisa Brooijmans,
Douglas A. Blank
et al.

Abstract: <b><i>Introduction:</i></b> Recent reports have raised concerns of cardiorespiratory deterioration in some infants receiving respiratory support at birth. We aimed to independently determine whether respiratory support with a facemask is associated with a decrease in heart rate (HR) in some late-preterm and term infants. <b><i>Methods:</i></b> Secondary analysis of data from infants born at ≥32<sup>+0</sup> weeks of gestation at 2 perinatal centres in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…However, even with the increasing use of ECGs, which have been shown to provide an HR faster than pulse oximetry [33], studies indicate that respiratory support is being initiated later. Badurdeen et al [37] showed that in late preterm and term infants with an anticipated need for resuscitation, respiratory support was initiated at a median (IQR) age of 63 (41-112) s. As there was a wide range of HRs when respiratory support was initiated, the authors speculated that insufficient respiratory efforts, rather than bradycardia, were common reasons for commencing positive pressure ventilation (PPV), which is in agreement with Kibsgaard et al [33].…”
Section: The Golden Minutementioning
confidence: 59%
See 1 more Smart Citation
“…However, even with the increasing use of ECGs, which have been shown to provide an HR faster than pulse oximetry [33], studies indicate that respiratory support is being initiated later. Badurdeen et al [37] showed that in late preterm and term infants with an anticipated need for resuscitation, respiratory support was initiated at a median (IQR) age of 63 (41-112) s. As there was a wide range of HRs when respiratory support was initiated, the authors speculated that insufficient respiratory efforts, rather than bradycardia, were common reasons for commencing positive pressure ventilation (PPV), which is in agreement with Kibsgaard et al [33].…”
Section: The Golden Minutementioning
confidence: 59%
“…Badurdeen et al [37] investigated the trigemino-cardiac reflex in late preterm and term infants and found that in initially depressed infants, the application of a facemask resulted in an increased not a decreased HR. These findings prompted the authors to speculate that the trigemino-cardiac reflex is suppressed in asphyxiated infants, i.e., those with a low or unstable baseline HR.…”
Section: Heart Rate In Hypoxemia and Asphyxiamentioning
confidence: 99%